Female political representation in the aftermath of ethnic violence: A comparative analysis of Burundi and Rwanda - Andrea Guariso; Bert Ingelaere; Marijke Verpoorten (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We study the impact of electoral gender quotas in post-war Burundi and Rwanda on women's political representation. First, we look at descriptive representation by studying the number of female representatives and the prestige of their positions in the legislative and executive branches of government. Second, we focus on political representation as perceived by ordinary women, before, during, and after the introduction of gender quotas. We find that, both in Rwanda and Burundi, descriptive female political representation significantly increased with the introduction of gender quotas, with the share of women in parliament and ministries consistently exceeding 30 per cent. While women still disproportionally end up in ministries of relatively lower prestige, the gap with men is closing as more women have joined the executive branches of power. We do not find any tangible effect on women's perceived political representation. Among the possible explanations, we discuss the authoritarian nature of the regime and the crowding out of gender identity by ethnic identity. We argue that these explanations are not entirely consistent with our data and put forward a third explanation, i.e. that the perception of political representation depends on the implementation of policies - thus substantive representation, not descriptive representation - and that men and women are to a very large extent appreciative of the same policies.
Keywords: D72; D74; K38; N47; Y8; 330; female political representation; gender quota; Rwanda; Burundi; life histories